HUBUNGAN KOORDINASI MATA DAN KAKI DENGAN KETERAMPILAN SEPAK SILA PERMAINAN SEPAKTAKRAW PADA TIM SEPAKTAKRAW SMAN OLAHRAGA RIAU - Juita, Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT,:this study was conducted to determine whether there is a relationship with a foot-eye coordination skills precepts football game sepaktakraw at SMAN team sports Riau province, so that at the time of soccer precepts can fondle, receive service delivery is sharp and fed the ball to Smasher well. The shape of this research is a correlation study, the population in this study is a team sport sepaktakraw sman Riau province, the sample in this study is a team sport sepaktakraw sman Riau and amounted to 15 people. Sampling technique that overall population (total sampling). The instruments used in this research is the eye and foot coordination test, which aims to measure eye coordination and foot then precepts soccer skills test that aims to measure the precepts soccer skills. After that, the data is processed with statistics, to test the normality of the test at a significant level 0,05α lilifors. The hypothesis is alleged there is a significant relationship between the eye and foot coordination with soccer skills precepts sepaktakraw game in team sports riau.Based on test analysis lilifors produce Lhitung (x) of 0.14 and 0.220 Ltabel, Lhitung (y) for 0 , 18 and Ltabel 0.220 means Lhitung <Ltabel, the sample comes from a population of normal berdristribusi. Then from the calculation of the product moment correlation between eye and foot coordination with the precepts soccer skills acquired rhitung 0.973 and 0.532 rtabel means rhitung> rtabel consequently Ha Ho is accepted and rejected.Thus there is a significant relationship between the eye and foot coordination with the precepts of games sepaktakraw soccer skills in team sports sman sepaktakraw Riau province. Keywords: eye coordination and foot, football skills